Remote Management of Heart Failure in Patients with Implantable Devices - Luca Santini; Francesco Adamo; Karim Mahfouz; Carlo Colaiaco; Ilaria Finamora; Carmine De Lucia; Nicola Danisi; Stefania Gentile; Claudia Sorrentino; Maria Grazia Romano; Luca Sangiovanni; Alessio Nardini; et al. (Diagnostics)
Background: Heart failure (HF) is a chronic disease with a steadily increasing prevalence, high mortality, and social and economic costs. Furthermore, every hospitalization for acute HF is associated with worsening prognosis and reduced life expectancy. In order to prevent hospitalizations, it would be useful to have instruments that can predict them well in advance. Methods: We performed a review on remote monitoring of heart failure through implantable devices. Results: Precise multi-parameter algorithms, available for ICD and CRT-D patients, have been created, which also use artificial intelligence and are able to predict a new heart failure event more than 30 days in advance. There are also implantable pulmonary artery devices that can predict hospitalizations and reduce the impact of heart failure. The proper organization of transmission and alert management is crucial for clinical success in using these tools. Conclusions: The full implementation of remote monitoring of implantable devices, and in particular, the use of new algorithms for the prediction of acute heart failure episodes, represents a huge challenge but also a huge opportunity.